Science and technology desk refrence : over 1,700 answers to frequently-asked or difficult-to-answer questions - Bobick, James E.; Peffer, Margery; Carnegie Library of Pittsburgh. Science and Technology Dept. (Detroit : Gale, 1996)
Questions are divided into twenty subject areas starting with "The animal world" and ending with "Weights, measures, and time.".
Includes bibliographical references (p. 685-719) and index.
Booklist.
Wilson's Junior High School.
Wilson's Senior High School.
Adult
Keywords: Science -- Miscellanea; Technology -- Miscellanea; Science -- Miscellanea; Technology -- Miscellanea